Potential of Trichoderma spp isolates as a growth promoter in tomato seedlings (Solanum lycopersicum) (Nexo Revista Científica, 2022)
Due to the need to produce healthy and high-quality food, current agricultural production systems are venturing into the use of sustainable and safer methods for pest control and improvement of plant nutrition. Among these methods, the use of the microbial biocontrol fungus Trichoderma spp. has been widely studied as a promoter of plant growth. However, in Nicaragua there are few studies on this genus. The present study aims to identify and quantify the potential of native isolates of Trichoderma spp., as promoters of growth and weight in tomato plantings. The conidia solution of Trichoderma spp. used during this study, was obtained from a diluted stock solution at a concentration of 108 conidia/ml, using 1 ml of solution in the seed substrate. Treatments evaluated were T1: T. harzianum; T12: T. asperelloide; T11c: T. viride; T8: T. songyi; F2TG-11: T. brevis; T3: T. asperellum; CIXD-07: T. virens. One milliliter of sterile distilled water was added to the control treatment (without inoculation). All trays were kept in the dark at 28±2°C. The variables to be measured were height, weight, length of the roots of seedlings, the measurement was made 25 days after emergence. Results demonstrate that, when compared with control treatment, the isolates of T. harzianum and T. viride show highest growth promoting potential, obtaining a gain of 38.8% and 22.6% in height, 72% and 46.3% in weight and 70% and 36.3% in root length, respectively.